Influence of Wet Cooling Vest on Firefihters' Protective Clothing (Journal of Fiber Bioengineering and Informatics, 2018)
Firefighters' Protective Clothing (FPC) is essential for protection against thermal and physical threats.FPC must be comfortable, enable heat transfer from the wearer to the environment and should notrestrict motion of body parts. The application of a cooling vest under protective clothing may preventoverheating by cooling at the microenvironment level while working in a hot environment duringfirefighting. In this study, the effect of using a passive system, in the form of a nonwoven fleece material,was investigated. This system was distributed across the surface of a vest on the upper front chest andback. In this passive system, hydro-crystals swell on contact with cold water, lowering body temperatureor holding the body temperature at a normal level. The thermal insulation of the wet and dry coolingvest was tested using a thermal manikin. Results showed that the thermal resistance of the systemdropped significantly due to replacement of dry air with moist air with higher thermal conductivity.This reduction was proportional to the amount of moisture present within the system.
Keywords: Cooling Vest; Firefighters' Protective Clothing; Thermal Manikin; Hydro-crystals